ANALISIS METODE MEMBACA CEPAT (SCANNING) DALAM PEMBELAJARAN BAHASA INDONESIA PADA KELAS IV SD - Muhammad Ilham Ardhiansyah Asydiq; Moh. Aniq KHB; Lina Putriyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Starting from where the times have started fast, technology is also getting fasterand increasing the governments attention to reading ability in Indonesia, whichcan be said to be low. A number of students still cannot identify the main idea inthe text and have a lack of understanding when reading. The purpose of thisresearch is to analyse the scanning method in Indonesian language learning ingrade IV of elementary school. This study applies descriptive qualitative methods,the data and data sources of this study are divided into 2, namely primary dataand secondary data, primary data is obtained from observation, interviews, andtests, while secondary data is obtained from documentation and teachingmodules. Primary data sources are obtained from teachers and students, whilesecondary data is obtained from books, theses and articles. The results of thereading speed of 20 students, 5 students were categorised as sufficient and 15students were categorised as good, so the total reading speed was 168 kpm witha good category. While the percentage data of reading content understanding thathas been calculated and entered into the reading content comprehensionpercentage formula, obtained results of 8 students can correctly answer 5questions out of 5 questions with a score of 100. Next 8 students can answer 4questions correctly with a score of 80. Next, as many as 4 students can answer 3questions with a score of 60. So the percentage of students understanding levelas a whole which is 84% is in the good category. So the speed reading method(scanning) in Indonesian language learning in grade IV of elementary school canbe applied because the speed reading method with this scanning technique isgood for students